High Bio-Content Thermoplastic Polyurethanes from Azelaic Acid - Rajput, Bhausaheb S.; Hai, Thien An Phung; Burkart, Michael D. (Molecules (Basel, Switzerland), 2022)
To realize the commercialization of sustainable materials, new polymers must be generated and systematically evaluated for material characteristics and end-of-life treatment. Polyester polyols made from renewable monomers have found limited adoption in thermoplastic polyurethane (TPU) applications, and their broad adoption in manufacturing may be possible with a more detailed understanding of their structure and properties. To this end, we prepared a series of bio-based crystalline and amorphous polyester polyols utilizing azelaic acid and varying branched or non-branched diols. The prepared polyols showed viscosities in the range of 504–781 cP at 70 °C, with resulting TPUs that displayed excellent thermal and mechanical properties. TPUs prepared from crystalline azelate polyester polyol exhibited excellent mechanical properties compared to TPUs prepared from amorphous polyols. These were used to demonstrate prototype products, such as watch bands and cup-shaped forms. Importantly, the prepared TPUs had up to 85% bio-carbon content. Studies such as these will be important for the development of renewable materials that display mechanical properties suitable for commercially viable, sustainable products.